Cryptoxyleborus brevicauda, a new species of xyleborine ambrosia beetle from Thailand (Coleoptera: Curculionidae: Scolytinae: Xyleborini) - Sittichaya, Wisut; Beaver, Roger A. (Zootaxa, 2024)
A new species, Cryptoxyleborus brevicauda Sittichaya & Beaver sp. nov., is described from the South of Thailand. A list of Cryptoxyleborus species found in Thailand with their provincial distributions and habitat types, and a key to Thai species are provided.